PEMANFAATAN PARKING STAND DI BANDAR UDARA HUSEIN SASTRANEGARA BANDUNG - Riza Lestari; Martha Ivanny; Indra Yuzal (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
The purpose of this study is to determine the effect of flight frequency development on parking stand utilization at Husein Sastranegara Airport in Bandung from 2014 to 2016. PT. Angkasa Pura II (Persero) manages 13 airports which one of them is Husein Sastranegara Airport in Bandung. The researchers want to find out whether there is influence of aviation frequency development on parking stand utilization at Husein Sastranegara Airport in Bandung from 2014 to 2016. The data collection was using field research or observation method and questionnaire. Techniques used to analyse the data were simple linear regression, correlation coefficient, coefficient determinant, and hypothesis test. From the result of the hypothesis test, it is known that the development of aviation frequency has a significant relationship to parking stand utilization.